IMPACT OF HUMAN ACTIVITIES ON KURUVIKKADU BIRDING SITE IN JAFFNA DISTRICT, SRI LANKA - Balachandran, C.; Thennakoon, T.M.S.P.K. (My University, 2019)
Jaffna peninsula consists of several ecosystems, and the wetlands play a vital role in the creation of good ecosystem balance and in maintaining healthy environmental condition of the area. The growing population has resulted in the reduction of natural habitats. This research was conducted in Kuruvikkadu wetland area of Jaffna district with the intention of identifying the human activities that threaten for the future persistence of Kuruvikadu birding site and propose suitable solutions to conserve this site. The required primary data were collected through field observation, questionnaire survey with fifty respondents, one structured interview and discussion with the officers of Central Environmental Authority, Wildlife Conservation Department, members of Ceylon Birds Club and the people from surrounding areas. The direct observations made in the study area primarily based on three months. The secondary data were obtained from records of relevant institutions, published research journals and authorised web data. Descriptive statistical techniques have been used to analyse the collected data. This study reveals that the Kuruvikkadu site is the habitat, breeding and feeding ground for more than twenty indigenous and migratory bird species, fish species, prawn, snail, small crab, shrimp, oyster, mollusc species, wild animals and has the favourable environmental conditions, potential natural resources to be a bird sanctuary. Even though this area is not declared as a sanctuary and presently facing serious threats to its survival mainly due to illegal deforestation, encroachment, unplanned development activities and fishing practices, improper waste disposal, hunting, lack of awareness and lack of institutional arrangements to declare this site as a sanctuary in the provincial and national level. It is an imperative need to declare this site as a sanctuary and conserve this wetland birding site to enrich the geo-environmental quality of the region, and appropriate activities should be undertaken by local people, the government institutions, and activist groups for the future persistence of this ecosystem. The research findings and recommendations derived from this study will be useful for environmental-related government agencies, non-government agencies, activist groups, researchers, planners, policymakers and graduates in Sri Lanka.
Keywords: bird sanctuary, human–bird conflicts, wetland ecosystem, sustainable management, persistence